Pemanfaatan Digital Marketing Untuk Meningkatkan Pendapatan UMKM Angkringan Di Wilayah Kemayoran - Riansyah, Ade; Widati, Endah (Shofanah Media Berkah, 2024)
The purpose of this study was to determine the use of digital marketing to increase angkringan income in the Kemayoran area. The research method used is a qualitative research method. The object of this study was angkringan businesses in the Kemayoran area as many as 8 angkringan businesses in the Kemayoran area. The data analysis technique used was triangulation analysis to test the validity of the data collected and descriptive analysis from miles & huberman. The results obtained from this study are that the use of digital media has a significant impact on the development of angkringan businesses. However, its effectiveness varies depending on the extent to which business owners actively and consistently utilize digital platforms. Business owners who actively use platforms such as Instagram, TikTok, and WhatsApp Business tend to experience increased revenue and customer interaction. Conversely, owners who are less active or only use Google Business do not experience a significant increase. Therefore, the use of digital marketing depends on the ability of business owners to manage digital media.